Imaging Genetics in Epilepsy: Current Knowledge and New Perspectives - Wang, Ge; Wu, Wenyue; Xu, Yuchen; Yang, Zhuanyi; Xiao, Bo; Long, Lili (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a neurological network disease with strong genetic components. Unfortunately, the relationship between genetic basis and imaging phenotype is by no means simple. Imaging genetics integrates multidimensional datasets within a unified framework, providing a unique opportunity to pursue a global vision for epilepsy. This review delineates the current knowledge of underlying genetic mechanisms for brain networks in different epilepsy syndromes, particularly from a neural developmental perspective. Further, endophenotypes and their potential value are discussed. Finally, we highlight current challenges and provide perspectives for the future development of imaging genetics in epilepsy.